Strychnan and secoangustilobine A type alkaloids from alstonia spatulata. Revision of the C-20 configuration of scholaricine - Kam, T.S.; Tan, S.J.; Low, Y.Y.; Choo, Y.M.; Abdullah, Z.; Etoh, T.; Hayashi, M.; Komiyama, K. (American Chemical Society and American Society of Pharmacognosy, 2010)
A total of 25 alkaloids were isolated from the leaf and stem-bark extracts of Alstonia spatulata, of which five are new alkaloids of the strychnan type (alstolucines A-E, 1-5)and the other, a new alkaloid of the secoangustilobine A type(alstolobine A, 6). The structures of these alkaloids were established using NMR and MS analysis and, in the case of alstolucine B (2), also confirmed by X-ray diffraction analysis. A reinvestigation of the stereochemical assignment of scholaricine (13) by NMR and X-ray analyses indicated that the configuration at C-20 required revision. Alkaloids 1, 2, 6, 7, 9, 10, and 13 reversed multidrug resistance in vincristine-resistant KB cells.